2011
DOI: 10.1016/j.pragma.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Pitch range, gestural information, and perceived politeness in Catalan

Abstract: It is known that certain prosodic aspects of speech play a role in the expression of paralinguistic meaning, yet the concrete mechanisms of how this is implemented have not yet been fleshed out. The present article attempts to explore the contribution of pitch range to the expression of politeness in information-seeking yes-no questions in Catalan. Two perception experiments were carried out with stimuli that contained a gradual increase and decrease of the pitch range at the end of two target intonation conto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The socio-pragmatic effects of rising boundary tones in Spanish and Catalán have been investigated in a couple of studies (Orozco 2008;Nadeu and Prieto 2011;Álvarez and Blondet 2003). However, these analyses, which were performed on elicited read-out speech and not on spontaneous data, have shown results that are not entirely unequivocal.…”
Section: Boundary Rises In Swedish and Spanishmentioning
confidence: 99%
“…The socio-pragmatic effects of rising boundary tones in Spanish and Catalán have been investigated in a couple of studies (Orozco 2008;Nadeu and Prieto 2011;Álvarez and Blondet 2003). However, these analyses, which were performed on elicited read-out speech and not on spontaneous data, have shown results that are not entirely unequivocal.…”
Section: Boundary Rises In Swedish and Spanishmentioning
confidence: 99%
“…These phenomena are suprasegmental, i.e., have effects on groups of linguistic items or segments, like phonemes. Literature has focused more on the suprasegmental/ prosodic expression of im/politeness (Roldán 2000;Culpeper et al 2003;Wichmann 2004;Hidalgo 2006;Lin et al 2006;Stadler 2006;Nadeu 2008;Orozco 2008;Grawunder and Winter 2010;Alvarez Muro et al 2011;Nadeu and Prieto 2011). The most frequently used parameters in the literature to carry out prosodic analyses are the following: (a) Pitch (melodic/intonation wave).…”
Section: Prosodic Featuresmentioning
confidence: 99%
“…Nadeu and Prieto (2011) manipulated the final pitch of each pattern in two perception experiments in regular steps and concluded that both intonation patterns were equally polite.…”
Section: Introductionmentioning
confidence: 99%